Service Learning Klinis Artikel Ilmiah Guru yang Akan Mengajukan Kenaikan Pangkat Jabatan - Ifit Novita Sari; Hayat Hayat (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of community service this time is first, helping the teacher's difficulties in writing scientific articles compiled from the results of Class Action Research (PTK) that has been done. Many results are obtained in teacher PTK and need to be published in order to be a reference for teachers and other educators. Second, for the promotion and class of teachers who have been promulgated in Permenegpan No. 16 of 2009 and Permendiknas No. 35 of 2010. Second, scientific articles written by teachers can be used for submissions for promotions and classes of teachers that have been promulgated in Permenegpan No. 16 of 2009 and Permendiknas No. 35 of 2010. Both candies require the calculation of the credit number of functional positions of teachers for the affairs of promotion and class. One of the credit figures is obtained from scientific publications. The target of this community service activity is to help teachers to hone their skills in terms of writing scientific articles and providing assistance / clinical scientific articles until published in the intended journal. The implementation of this activity is scheduled for three months, starting from: (1) giving material, (2) introducing and providing examples of scientific articles that have been published in national and international journals, (3) accompanying teachers in writing scientific papers compiled from the results of PTK, (4) helping teachers to assess the extent to which their scientific writing is worth publishing, and (5) helping to give directions to which journals will be intended to publish their work.